PENGARUH STRATEGI BISNIS DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI MANAJEMEN (Studi pada PT. Pos Indonesia Bandung) - Indriani Fitri Hidayat (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2018)
Business strategy and environmental uncertainty are popular and complex concepts that are identified as factors that can affect the quality of management accounting information systems. The phenomenonthat accurs in Indonesia is teh quality of management accounting information system that has not been perfect. Similarly, business strategy and environmental uncertainty have not shown the ideal conditions. This study aims to achieve the truth through testing (confirmation) the infulence of business strategy and environmental uncertainty on the quality of management accounting information system at PT. Pos Indonesia Bandung. The data used is obtained through survey by distributing questionnaires at PT. Pos Indonesia Bandung, processed statistically with the help of Smart-PLS software. The method used in this research is descriptive analysis method verifikatif. The result of this study indicate: (1) Business Strategy have a significant positive effect onthe quality of management accounting information system. (2) environmental uncertainty have a significant positive effect on the quality of management accounting information system.